Association of entry into hospice or palliative care consultation during acute care hospitalization with subsequent antibiotic utilization. (January 2023) - Marra, Alexandre R.; Clore, Gosia S.; Balkenende, Erin; Goedken, Cassie Cunningham; Livorsi, Daniel J.; Goto, Michihiko; Vaughan-Sarrazin, Mary S.; Broderick, Ann; Perencevich, Eli N.
Abstract: Objective: We aimed to estimate antibiotic use during the last 6 months of life for hospitalized patients under hospice or palliative care and identify potential targets (i.e. time points) for antibiotic stewardship during the end-of-life period. Methods: We conducted a retrospective cohort study of nationwide Veterans Affairs (VA) patients who died between January 1, 2014 and December 31, 2019 and who had been hospitalized within 6 months prior to death. Data from the VA's integrated electronic medical record were collected, including demographics, comorbid conditions, and duration of inpatient antibiotics administered, along with outpatient antibiotics dispensed. A propensity score–matched cohort analysis was conducted to compare antibiotic use between hospitalized patients placed into palliative care or hospice matched to hospitalized patients not receiving palliative care or hospice. Results: There were 9808 and 40 796 propensity score–matched patient pairs in the hospice and palliative care groups, respectively. Within 14 days of placement or consultation, 41% (4040/9808) of hospice patients and 48% (19 735/40 796) of palliative care patients received at least one antibiotic, while 25% (2420/9808) matched nonhospice and 27% (10 991/40 796) matched nonpalliative care patients received antibiotics. Entry into hospice was independently associated with a 12% absolute increase in antibiotic prescribing, and entry into palliative care was associated with a 17% absolute increase during the 14 days post-entry vs. pre-entry period. Discussion: We observed that patients receiving end-of-life care had high levels of antibiotic exposure across this VA population, particularly during admissions when they received hospice or palliative care consultation.